2020
DOI: 10.21511/ppm.18(4).2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of key university leadership factors based on their international rankings (QS World University Rankings and Times Higher Education)

Abstract: In the context of globalization of the educational services market, competition between universities is becoming more intense. This manifests itself, among other things, in the struggle for positions in international university rankings. Given that universities are evaluated according to many criteria in such rankings, it becomes necessary to identify the most significant factors in determining their positions.This study aims to identify the key factors determining the world’s leading universities’ leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…An arboretum can even be an example of a research center. It provides comprehensive opportunities for practical teaching (Kumar, et al, 2021;Mohanu et al, 2022;Kuzior et al, 2022aKuzior et al, , 2022bMidor et al, 2021;Polyakov et al, 2019, implement some key aspects of the activities of European higher education institutions in the domestic educational process (Polyakov et al, 2020). The state financing of higher education institutions is complex and requires a comprehensive approach to forming its optimal volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An arboretum can even be an example of a research center. It provides comprehensive opportunities for practical teaching (Kumar, et al, 2021;Mohanu et al, 2022;Kuzior et al, 2022aKuzior et al, , 2022bMidor et al, 2021;Polyakov et al, 2019, implement some key aspects of the activities of European higher education institutions in the domestic educational process (Polyakov et al, 2020). The state financing of higher education institutions is complex and requires a comprehensive approach to forming its optimal volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…University leaders and administrators are gaining even more experience in working with rankings (Rauhvargers, 2014). From a management and marketing standpoint, there is a practical need to compare the rankings and the numerical values of various criteria based on which they are compiled (Polyakov et al, 2020) to steer decision making and incorporate changes where necessary. Many universities establish institutional policies for communicating with ranking providers and appoint a staff member who follows both trends in the ranking and the success of rival universities.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, short-term gains to perform better in ranking are encouraged at the expense of meaningful activities that are not measured by global rankings. Polyakov et al (2020) discusses university rankings within the context of globalization of the educational services market in which competition between universities is becoming more intense. International rankings are considered as a reflection of universities' competitiveness in the global market.…”
Section: Are Rankings Helpful To Achieve Mission Of He?mentioning
confidence: 99%
“…This literature review identified that 20% of studies addressed university rankings from a global perspective [5,9,11,12,18,20,28,31,34,35,[44][45][46][47]49,51,[55][56][57][58].…”
Section: Regions and Nations Involved In The Study Of Global Universi...mentioning
confidence: 99%
“…Times Higher Education (THE) and QS World University Rankings [18,27,28,33,44,47] Academic UI Green Metric World University Ranking (WUR) and Times Higher Education World University Rankings (THE-WUR). [13] ISC World University Ranking (ISC WUR) Leiden Ranking Nature Index, Times Higher Education (THE), and Quacquarelli Symonds (QS).…”
Section: University Rankings Authorsmentioning
confidence: 99%